Journalism next a practical guide to digital reporting and publishing - Briggs, Mark 1969- (SAGE, 2020)
The fourth edition of Journalism Next is updated with the latest technological innovations and media industry transformations, ensuring that Mark Briggs' proven guide for leveraging digital technology to do better journalism keeps pace with ongoing changes in the media landscape. To keep ahead and abreast of these ever-evolving tools and techniques, Briggs offers practical and timely guidance for both the seasoned professional looking to get up to speed and the digital native looking to root their tech know-how in real journalistic principles Learn how to effectively blog, crowdsource, use mobile applications, mine databases, and expertly capture audio and video to report with immediacy, cultivate community, and tell compelling stories. Journalism Next will improve digital literacy--fast. Briggs starts with the basics and then explores specialized skills in multimedia so you can better manage online communities and build an online audience. Journalism Next is a quick read and roadmap you'll reference time and time again. Dive into any chapter and start mastering a new skill right away. And for today's journalist, who can afford to waste any time?"--